Answer:
- y= -12
- x = 7
- q = -1
- x = 24
Step-by-step explanation:
1. ..............................................
- 6(y + 7) = 2(y - 3)
- 6y + 42 = 2y - 6
- 6y - 2y = -6 - 42
- 4y = -48
- y = -12
2...............................................
- 3x + 2(x - 5) = 25
- 3x + 2x - 10 = 25
- 5x = 25 + 10
- 5x = 35
- x = 7
3 . ..............................................
- 10q + 3q + 5 = 2(q - 3)
- 13q + 5 = 2q - 6
- 13q - 2q = -6 - 5
- 11q = -11
- q = -1
4. ..............................................
- 1/3(x + 6) = 2/3(x - 9)
- 3*1/3(x+6) = 3*2/3(x - 9)
- x + 6 = 2(x - 9)
- x + 6 = 2x - 18
- 2x - x = 6 + 18
- x = 24
Answer:
its c, y = one eighthx2 + 1
Step-by-step explanation:
Answer:
he usual definition is that every face must have the same number of edges, and the same number of faces must meet at every vertex. The key to most proofs of this classification is the Euler characteristic.
Step-by-step explanation:
Answer:
54
Step-by-step explanation:
4x11-(17) 4x11-(17)
44-17 44-17
27 + 27
54